Karakteristik Penerima Manfaat Program BAZNAS Untuk Bantuan Modal Usaha Mikro Di Kabupaten Ciamis - Fahriza, Chintya Ayudia; Ahmad, Abdul; Bambang, Bambang (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Bantuan Modal Usaha Kecil (BMUK) is one of the programs in the economic field at the National Amil Zakat Agency (BAZNAS) in Ciamis Regency, which carries out activities by providing capital assistance to micro-enterprises. With this business capital assistance program, it is hoped that microenterprises can feel the benefits after receiving capital assistance from BAZNAS where from receiving the assistance provided, the business concerned can continue to develop. The purpose of this study is to analyze the characteristics of the beneficiaries of the BAZNAS Bantuan Modal Usaha Kecil (BMUK) program in Ciamis Regency. This research was conducted in Ciamis Regency with 39 micro business actors as respondents. The study used primary data with observation, interview, and questionnaire collection techniques. Then the data obtained were analyzed using Descriptive Statistics. The results of this study conclude that the characteristics of the beneficiaries of the Small Business Capital Assistance (BMUK) program vary, consisting of length of business, household income and expenses, last education, age of respondents, line of business, and number of dependents in the family. The National Amil Zakat Agency of Ciamis Regency is also expected to be right on target in providing assistance to micro business actors by consistently monitoring and evaluating micro business actors so that business actors experience business development so that the purpose of the Bantuan Modal Usaha Kecil (BMUK) program is to improve the welfare of the perpetrators. micro-enterprise can be achieved